ANALISIS REVIEW PENGGUNAAN MEDIA CERITA BERGAMBAR UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA SEKOLAH DASAR - Arzeti, Andrean Seva Arzeti; Edwita; Dina Rahmi Darman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading comprehension is one of the essential language skills that elementary school students need to master, yet in practice many students still struggle to grasp the meaning of texts they have read. This study aims to examine and analyze the effectiveness of picture story media in improving elementary school students' reading comprehension skills through a systematic literature review approach. Article searches were conducted through Google Scholar, Garuda, and SINTA databases using relevant keywords, limited to publications from 2022 to 2026. The selection process followed the PRISMA flow consisting of identification, screening, eligibility assessment, and final article determination stages, resulting in 15 articles that met the inclusion criteria. The articles were analyzed qualitatively and descriptively by comparing research objectives, methods, subjects, and findings across studies. The results showed that picture story media consistently proved effective in improving reading comprehension across various research approaches, including classroom action research, experimental studies, and research and development. Significant improvements in learning outcomes were recorded in nearly all studies reviewed, with effect sizes ranging from moderate to very large. Several factors were found to influence the effectiveness of this media, including design quality, teacher guidance during the learning process, and the appropriateness of the content for students' grade level and characteristics. This study concludes that picture story media, whether in printed or digital form, is a relevant and effective choice for supporting reading comprehension learning in elementary schools, and recommends its broader implementation alongside further longitudinal research to assess long-term impacts on student literacy development.